The structure and occurrence of a velum in Utricularia traps (Lentibulariaceae) - Płachno, Bartosz J.; Świątek, Piotr; Miranda, Vitor F. O. [UNESP]; Stolarczyk, Piotr (Frontiers, 2019)
Bladderworts (Utricularia, Lentibulariaceae, Lamiales) are carnivorous plants that form small suction traps (bladders) for catching invertebrates. The velum is a cuticle structure that is produced by specialized trichomes of the threshold pavement epithelium. It is believed that the velum together with the mucilage seals the free edge of the trap door and that it is necessary for correct functioning of the trap. However, recently, some authors have questioned the occurrence of a velum in the traps of the Utricularia from the various sections. The main aim of this study was to confirm whether velum occurs in the traps of the Utricularia species from the subgenera Polypompholyx, Bivalvaria, and Utricularia. The 15 species were examined from subg. Polypompholyx, subg. Bivalvaria, and subg. Utricularia. A velum was found in all examined Utricularia species. In the traps of the members of section Pleiochasia, there was an outer velum (forming a complete ring) and an inner velum. In the traps of Utricularia uniflora (Lasiocaules), there was only an inner velum. In these species, the formation of the velum was accompanied by intensive mucilage production, and as a result, when door was closed (set position), the mucilage and the velum touched the surface of the door. In members of both sections of Pleiochasia and Lasiocaules, the pavement epithelium had a more complicated structure (four to five zones) than in the members of the subgenera Bivalvaria and Utricularia in which three distinct zones occurred (an outer with a velum, a middle and an internal with the mucilage trichomes). Even in U. purpurea, where the threshold was a reduced pavement epithelium, it consisted of three functional zones and the presence of a velum. Two main types of velum have been proposed. A velum was present in Utricularia traps regardless of the trap type or the habitat (aquatic, epiphytic, and terrestrial species). We proposed broad definition of velum as cuticle membranes covered by mucilage; from a functional point of view, this definition is more useful and more reflects complexity of this structure.
Keywords: Bivalvaria; Carnivorous plants; Functional anatomy; Functional morphology; Polypompholyx; Trap; Utricularia